Carbon materials for hydrogen storage: A bibliometric analysis on current trends and future prospects - Saeid, Mohammed Faraj; Abdulkadir, B. A.; Muhammad Ashraf, Fauzi; Herma Dina, Setiabudi (John Wiley and Sons Inc., 2025)
This article offers an overview of bibliometric analysis of carbon materials for hydrogen storage (CMHS) research over the past 33 years, from January 1991 to April 2024. A total of 3544 research papers centered on carbon-based hydrogen storage materials were analyzed. The analysis encompassed various aspects, including the countries where publications originated, authors' affiliations, prominent journals, research areas, and key terms driving discussions in the field. The research findings reveal a rising significance of carbon-based hydrogen storage materials studies. China leads the top 10 countries in the number of research papers, contributing 1124 publications. When considering the Total Link Strength metric, which reflects international collaborative efforts, China, the United States, and India ranked first, second, and third, respectively, demonstrating their substantial engagement in global collaborations. The International Journal of Hydrogen Energy is prominent for its significant publication volume, totaling 679 articles. Research trends have progressed, initially concentrating on carbon nanotubes and graphene, shifting to activated carbons, and ultimately focusing on confining MgH2 within carbon-based materials for hydrogen storage applications. Current challenges include low hydrogen volumetric density and the need for improved desorption kinetics at ambient conditions. Future research should focus on developing novel carbon composites, optimizing synthesis methods, and leveraging machine learning for material discovery.